2009
DOI: 10.4028/www.scientific.net/amr.69-70.88
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Diamond-Cutting Surface by Means of Porous Bearing Laminar Flow

Abstract: Air bearings had been widely used in ultra-precision machine tools. In order to suppress the micro-vibration caused by air bearing, an effective way is keeping the air flow in laminar state. Porous bearing to control the micro-vibration was proposed in this paper, and the related experiments show that it can meet the requirement of decreasing the micro-vibration to less than 1nm, and the surface of diamond surface can be improved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…A rounded corner of the orifice outlet (Aoyama et al., 2006) was also claimed to be effective in suppressing the vortex flow and nano-vibration of the bearing. He et al. (2009) showed that porous restrictors can easily achieve flow laminarization and hence reduce nano-vibration of aerostatic bearings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A rounded corner of the orifice outlet (Aoyama et al., 2006) was also claimed to be effective in suppressing the vortex flow and nano-vibration of the bearing. He et al. (2009) showed that porous restrictors can easily achieve flow laminarization and hence reduce nano-vibration of aerostatic bearings.…”
Section: Introductionmentioning
confidence: 99%
“…A rounded corner of the orifice outlet (Aoyama et al, 2006) was also claimed to be effective in suppressing the vortex flow and nano-vibration of the bearing. He et al (2009) showed that porous restrictors can easily achieve flow laminarization and hence reduce nano-vibration of aerostatic bearings. However, these methods are often limited by manufacturing capabilities: for example, porous restrictors with uniform pores with low permeability (<10 À12 m 2 ) are very difficult to manufacture.…”
Section: Introductionmentioning
confidence: 99%